T The Impact Of Job Security And Work Engagement Onto Organization Commitment: A Case Study Of Tenured Faculty Of Universitas Islam Negeri (Uin) Syarif Hidayatullah Jakarta - Rochimah Imawati (Institute of Computer Science (IOCS), 2022)
Hypothetically, employees will be committed to their organizational obligation and responsibility if their job are secure and they are highly engaged in their works, and their organizational commitment in turn benefits the company for which they work. However, this hypothesis must be first validated and its truth must be first justified so that it becomes a scientific fact. This study aims at proving the hypothesis validity of the effect of job security and work engagement onto organizational commitment. To do so, 60 (sixty) persons of tenured faculty of FIDIKOM (Faculty of Computer Education) were taken as research sample. This study uses a quantitative method with a descriptive and verification approach, while the sampling technique used is purposive sampling by incidental sampling. The research instrument in this study is a questionnaire, the results of which are in the form of a scale. The scale uses a Likert scale. The hypothesis testing in this study uses Moderated Regression Analysis (MRA). The results showed that Job Security had a significant/significant effect on Organizational Commitment. Work engagement has a significant/significant effect on Commitment Organization. Job Security, Work Engagement, and Moderation have a significant/significant effect on Organizational Commitment.